Blockchain applications on mobile device - Chong, Jordan Sia (Nanyang Technological University, 2022)
Identity management is an essential part of society yet it is riddled with problems and inefficiencies. This document reports on a digital identity project that takes advantage of the Ethereum blockchain to simplify and automate identity management while making it more robust against theft and fraud. The report contains the details of a Credentials smart contract implemented in solidity. It also discusses the Identity website and the Identity mobile app which allow schools, students and verifiers to interact with the Credentials smart contract. The report also includes code snippets, screenshots and explanations of the implementation of the Credentials smart contract, Identity website and Identity mobile app. Lastly, it includes some potential expansion features.